2020
DOI: 10.1002/pbc.28237
|View full text |Cite
|
Sign up to set email alerts
|

Congenital neutropenia with variable clinical presentation in novel mutation of the SRP54 gene

Abstract: All coauthors have reviewed the manuscript and have contributed in a substantive and intellectual manner to the work described. * Orna Steinberg-Shemer and Raz Somech had equal contribution. AbstractBackground: The SRP54 (signal recognition protein 54) is a conserved component of the ribonucleoprotein complex that mediates cotranslational targeting and translocation of proteins to the endoplasmic reticulum. In 2017, mutations in the gene have been described as a cause of congenital neutropenia with or without … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…SRP54 (Signal Recognition Particle 54) is a part of signal recognition particle (SRP), a ribonucleoprotein, that mediates the passage between the ribosomes and membrane associated protein-translocation machinery of the endoplasmic reticulum (ER). Recently, Goldberg et al reported a novel mutation (in frame deletion) that affects complex stability causing congenital neutropenia [ 45 ], as described also in previous studies [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…SRP54 (Signal Recognition Particle 54) is a part of signal recognition particle (SRP), a ribonucleoprotein, that mediates the passage between the ribosomes and membrane associated protein-translocation machinery of the endoplasmic reticulum (ER). Recently, Goldberg et al reported a novel mutation (in frame deletion) that affects complex stability causing congenital neutropenia [ 45 ], as described also in previous studies [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 84%
“…The mutation-dependent effect on GTP binding affinity can be correlated with the clinical phenotypes of patients. When considering all cases that have been reported so far in the literature, the majority of patients with mutations in the G1 element show milder phenotypes than those with mutations in the other G elements or in the ''GQ '' motif (Bellanne ´-Chantelot et al, 2018;Chippaux, 1987;Goldberg et al, 2020;Saettini et al, 2020). As patients are heterozygous, it is likely that mutations in the G1 element (T115A and T117del) that decrease the binding affinity for GTP interfere less efficiently with the function of the remaining WT copy of the protein than mutations affecting other regions and linked to other functional defects.…”
Section: Discussionmentioning
confidence: 99%
“…One additional patient, presenting with familial neutropenia and recurrent infections, was subsequently diagnosed by WES with a novel SRP54 variant causing SCN and SBDS. 25 , 36 This gene was not known to cause neutropenia at the time the NGS study was performed. We later incorporated this gene into the subsequent versions of our NGS panel and detected a variant in this gene in one more patient that had a re-do of the NGS panel.…”
Section: Resultsmentioning
confidence: 99%